Method for the determination of thyreostats in milk samples using LC-MS/MS - Církva, Aleš; Šťastný, Kamil (Food additives & contaminants. Part A, Chemistry, analysis, control, exposure & risk assessment, 2013)
A sensitive and selective analytical method for the determination of four thyreostats (tapazol, thiouracil, methylthiouracil and propylthiouracil) in cow's milk, lamb's milk, and goat's milk was developed and validated according to 2002/657/EC criteria. Proteins in milk samples were precipitated by acetonitrile and analytes were derivatised with 3-iodobenzylbromide. Afterwards, derivatives were separated from the matrix by liquid-liquid extraction with ethyl acetate as an organic solvent and analysis was carried out using LC-MS/MS in a positive electrospray mode. The method provides, for all determined analytes, decision limits CCα below 1 ng ml(-1) and a detection capability CCβ value below 1.5 ng ml(-1). The stability of analytes in sample extracts stored at various conditions was also tested and evaluated.
Keywords: Milk; thyreostatika; mléko; tandemová hmotnostní spektrometrie; zvířata; Chromatography, Liquid; Antithyroid Agents; Tandem Mass Spectrometry; chromatografie kapalinová; Animals